If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + -2y = 6 Combine like terms: 2y + -2y = 0 0 = 6 Solving 0 = 6 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| lg(4x^2+7)=2 | | 16/21•-7/8 | | 12x-6=15x+9 | | 5/7x2/7 | | 2.3333z+3.666=1.3333(z+3.666) | | b-2b=3 | | 2z^6+5z^3-12=0 | | 15+x=30-2x | | 2x-4(4-3x)=x+10 | | 2x-4=4-3x | | 5b+22=2 | | 41-3b=32 | | 9b-4=50 | | 4x^2+-3x+-10= | | 7/3y-5/3=1/3(y-8/3) | | 3x*2-3=0 | | 13=2y-11 | | 5(t+3)=3(2t+1) | | 4v+15=43 | | 8m^2+m=2 | | (8x^2y^2-4x^2y-12xy)/4xy | | (2x-3)/2=(3x-8)/2 | | 2x-17=4+17 | | (2x-3)/2=(3x-8)/3 | | 4r^2-4=172 | | 33=2x+14 | | 4r^2=172 | | 5m^2-24m^2=0 | | 4x^2-15x-4x^3=0 | | 12a+8=20 | | 35+8x=3 | | 35+8x =3 |